Emerging role of SIRT3 in mitochondrial dysfunction and cardiovascular diseases. (1st February 2019) - Wu, Jie; Zeng, Zhenhua; Zhang, Weijin; Deng, Zhiya; Wan, Yahui; Zhang, Yaoyuan; An, Sheng; Huang, Qiaobing; Chen, Zhongqing
Abstract: As a nicotinamide adenine dinucleotide (NAD) + -dependent protein deacetylase, SIRT3 is highly expressed in tissues with high metabolic turnover and mitochondrial content. It has been demonstrated that SIRT3 plays a critical role in maintaining normal mitochondrial biological function through reversible protein lysine deacetylation. SIRT3 has a variety of substrates that are involved in mitochondrial biological processes such as energy metabolism, reactive oxygen species production and clearance, electron transport chain flux, mitochondrial membrane potential maintenance, and mitochondrial dynamics. In the suppression of SIRT3, functional deficiencies of mitochondria contribute to the development of various cardiovascular disorders. Activation of SIRT3 may represent a promising therapeutic strategy for the improvement of mitochondrial function and the treatment of relevant cardiovascular disorders. In the current review, we discuss the emerging roles of SIRT3 in mitochondrial derangements and subsequent cardiovascular malfunctions, including cardiac hypertrophy and heart failure, ischemia-reperfusion injury, and endothelial dysfunction in hypertension and atherosclerosis.